Electrospinning Superhydrophobic and Antibacterial PS/MWNT Nanofibers onto Multilayer Gas Barrier Films. Issue 1 (August 2017) - Tiu, Brylee David B.; Nguyen, Hang N.; Rodrigues, Debora F.; Advincula, Rigoberto C.
Abstract : In this work, we demonstrate the non‐synthetic surface modification of a co‐extruded multilayer poly(methyl methacrylate) (PMMA)/poly(ϵ‐caprolactone) (PCL) film with gas barrier properties through electrospinning of polystyrene (PS)/multi‐walled carbon nanotube (MWNT) nanofibers. As produced by forced assembly layer multiplying co‐extrusion, the heterogeneous nucleating crystallization of PCL was induced using the glassy confinement of the amorphous PMMA thus creating in‐plane lamellae crystallization, which is impermeable to most gas molecules. To complement these intrinsic gas barrier properties of the multilayer film, electrospun PS/MWNT nanofibers were deposited onto the surface of the PMMA/PCL film, which increased the surface roughness and resulted in superhydrophobic behavior (water contact angles>150°). Furthermore, the inclusion of the MWNT in the matrix caused an increasing antibacterial efficacy, which was determined to reach 97% inactivation against gram‐positive bacteria Bacillus subtilis . The fiber mats were further characterized using scanning electron microscopy (SEM), Raman spectroscopy, and thermogravimetric analysis (TGA).